Clinical and Epidemiological Characterization of Acute Chagas Disease in Casanare, Eastern Colombia, 2012–2020 - Rincón-Acevedo, Claudia Yaneth; Parada-García, Andrea Stella; Olivera, Mario Javier; Torres-Torres, Fernando; Zuleta-Dueñas, Liliana Patricia; Hernández, Carolina; Ramírez, Juan David (Frontiers in Medicine, 2021)
Background: Chagas disease (CD), caused by the protozoan Trypanosoma cruzi is considered a public health problem in Latin America. In Colombia, it affects more than 437,000 inhabitants, mainly in Casanare, an endemic region with eco-epidemiological characteristics that favor its transmission. The objective of this study was to describe the clinical and epidemiological characteristics of the cases of acute CD in Casanare, eastern Colombia in the period 2012-2020. Methods: In the present study, 103 medical records of confirmed cases of acute CD were reviewed. The departmental/national incidence and fatality were compared by year; the climatological data of mean temperature, relative humidity and precipitation per year were reviewed and plotted at IDEAM (Colombian Meteorology Institute) with respect to the number of cases of acute CD per month and it was compared with the frequency of triatomines collected in infested houses by community surveillance. Univariate, bivariate, and multivariate analyzes were performed, comparing symptoms and signs according to transmission route, complications, and age groups. Results: The incidence was 3.16 cases per 100,000 inhabitants and the fatality rate was 20% in the study period. The most frequent symptoms included: fever 98.1%, myalgia 62.1%, arthralgia 60.2%, and headache 49.5%. There were significant differences in the frequency of myalgia, abdominal pain and periorbital edema in oral transmission. The main complications were pericardial effusion, myocarditis and heart failure in the group over 18 years of age. In Casanare, TcI DTU has mainly been identified in humans, triatomines and reservoirs such as opossums and dogs, as well as TcBat in bats. An increase in the number of acute CD cases was evidenced in the month of March, a period when precipitation increases due to the beginning of the rainy season. Conclusions: The results corroborate the symptomatic heterogeneity of the acute phase of CD, which delays treatment, triggering possible clinical complications. In endemic regions, clinical suspicion, diagnostic capacity, and detection and surveillance programs should be strengthened, as well as intersectoral public health policies for their prevention and control.